The guinea pig - Chetham-Strode, Warren 1896-1974; Wooldridge, John 1919-1958 (British Film Institute, 2020)
"Richard Attenborough (Brighton Rock) is Jack Read, a working-class boy and the guinea pig of the title, who is given a scholarship to Saintbury, an exclusive public school. Faced with the snobbery of his new classmates, he tries to gain acceptance from not only them, but also some of his teachers. Also known as "The Outsider", "The Guinea Pig" was made in 1948, four years after the publication of The Fleming Report. Co-starring Sheila Sim, Bernard Miles and Joan Hickson the film has been newly remastered in 2K by the BFI." [bfi.org/uk]
Original: Großbritannien 1948
special features: newly remastered by the BFI and presented in High Definition and Standard Definition ; "Old school" (1905-1987, 71 mins): learn all about British education as seen on screen – from Edwardian board school parades to 1980s comprehensive kids getting to grips with GCSEs – with a century-spanning selection of rare documentary films from the BFI National Archive ; "The Make-Do-And-Menders" (1941-1945, 24 mins): recall the ration-book world that provided the real-life social background for "The guinea pig" in this eccentric assortment of archive oddities from the war years ; image gallery
Keywords: Film